El bilingüismo en la Universidad Pedagógica Nacional, Colombia : experiencias pioneras en la clase de ciencias con estudiantes de pregrado. (2014)
The Bilingualism experience for teaching physics was carried out in the second course of electromagnetism at the physics department of the Universidad Pedagogica Nacional. It was developed with second year students of the Bachelor of Science in physics. Ten sessions of the entire course were developed in English; devoted to analyze Faradays law based in electromagnetic field point of view. One physics teacher and an English teacher were in charge of the course. The students were immersed into the bilingual context. Furthermore, they were able to understand faradays law and concepts. Understanding level was moderate-medium. The majorant disequilibrium was presented and let students take part in to the bilingual activity improving confidence between them. Originals Maxwell text has been understood in first steps.